Analisis Faktor yang Mempengaruhi Kepuasan Pasien Dalam Pelayanan Kesehatan Dasar di UPTD Puskesmas Pagelaran Pringsewu - Nia Dayasih; Samino Samino; Fitri Eka Sari; Christin Angelina Febriani; Riyanti Riyanti (Malahayati Nursing Journal, 2025)
ABSTRACT Quality health services are an important factor in achieving patient satisfaction. Low patient satisfaction depends on the quality of services provided. Patients will feel satisfied if there is equality between expectations and the reality of the health services they receive. The level of patient satisfaction at the UPTD Pagelaran Pringsewu Health Center is still low, so researchers are interested in analyzing patient satisfaction in basic health services at the Pagelaran Pringsewu Health Center. Objective To analyze patient satisfaction in basic health services at the Pagelaran Pringsewu Health Center. This type of quantitative research uses a cross-sectional approach. The population of the study was outpatients at the Pagelaran Pringsewu Health Center using the probability accidental sampling technique. The research sample was 161 respondents. The research instrument was a questionnaire. Data analysis used for Partial Least Square (PLS) analysis using SmartPLS software. The results of the study showed that there was an influence of physical evidence (Path Coefficient 0.123 t statistic 2.269), responsiveness (Path Coefficient 0.268 t statistic 3.389), empathy (path Coefficient 0.325 t statistic 5.268), assurance (path Coefficient 0.116 t statistic 2.754), reliability (path Coefficient 0.235 t statistic 3.462) on work motivation. The suggestion in this study is that the Health Center creates patient satisfaction and the services provided are not in accordance with what the patient expects, the way that can be taken is by improving the quality of human resources. Keywords: Satisfaction, Patients, Outpatient, Pagelaran Pringsewu Health Center  ABSTRAK Pelayanan kesehatan yang bermutu merupakan faktor yang penting dalam mencapai kepuasan pasien. Kepuasan pasien rendah tergantung dengan kualitas pelayanan yang diberikan. Pasien akan merasa puas apabila ada persamaan antara harapan dan kenyataan pelayanan kesehatan yang diperoleh. Masih rendahnya tingkat kepuasan pasien di UPTD Puskesmas Pagelaran Pringsewu maka peneliti tertarik untuk menganalisis kepuasan pasien dalam pelayanan kesehatan dasar di UPTD Puskesmas Pagelaran Pringsewu. Tujuan penelitian untuk menganalisis kepuasan pasien dalam pelayanan kesehatan dasar di UPTD Puskesmas Pagelaran Pringsewu. Jenis penelitian kuantitatif dengan pendekatan cross sectional. Populasi penelitian pasien rawat jalan di UPTD Puskesmas Pagelaran Pringsewu teknik probability accidental sampling. Sampel penelitian 161 responden. Instrumen penelitian adalah kuesioner. Analisa data yang digunakan untuk analisa Partial Least Square (PLS) dengan menggunakan software SmartPLS. Hasil penelitian menunjukkan ada pengaruh bukti fisik (Path Coefficient 0,123 t statistik 2,269), daya tanggap (Path Coefficient 0,268 t statistik 3,389), empati (path Coefficient 0,325 t statistik 5,268), jaminan (path Coefficient 0,116t statistik 2,754), kehandalan (path Coefficient 0,235 t statistik 3,462) terhadap motivasi kerja. Saran pada penelitian ini Puskesmas menciptakan sebuah kepuasan pasien dan pelayanan yang diberikan belum sesuai apa yangdiharapkan pasien, cara yang bisa ditempuh adalah dengan peningkatan kualitas SDM.  Kata Kunci: Kepuasan, Pasien, Rawat Jalan, Puskesmas Pagelaran Pringsewu